Knapik, Aleksandra R., Piotr P. Chruszczewski (2023) Kreolingwistyka w zarysie. Językowo–kulturowe mechanizmy przetrwania, rozwoju i dezintegracji Seria: Beyond Language Vol. 8., San Diego, CA: Academic Publishing; ss. 301 - Giwojno, Paweł (2023)
The authors of the book are focused on the field of creolinguistics: a relatively new but rapidly developing domain of science located within the frameworks of anthropological linguistics. The main aim of the book is to describe thoroughly the location of creolinguistics, in general, from the viewpoint of anthropological linguistics, and in particular, analyzing the key concepts and entire methodological apparatus used by creolinguists. In the first chapters, an outline focused on a new taxonomy of linguistic anthropology is proposed with a particular place given to creolinguistics. In the following chapters, a precise study of the main components of creolinguistics, as well as its theoretical background and numerous references to practical examples are given. Finally, in a broad section, an extensive list of the literature focused on creolinguistics, as well as three types of indexes are delivered. All in all, the comprehensive knowledge contained within, broadly explained with numerous references to real life examples and vivid language, makes this book an excellent academic work which may be used by both processional linguists and students interested in broadening their horizons. Moreover, equally important is the fact that this is the first academic book focused on creolinguistics fully in Polish which makes it both a unique and fundamental work for further generations of linguists.
Keywords: creolinguistics; contact linguistics; language; culture; pidgin; creole